2010
DOI: 10.1038/sj.bjc.6605644
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between telomere shortening, genetic instability, and site of tumour origin in colorectal cancers

Abstract: BACKGROUND: Telomeres, located at chromosome ends, are progressively shortened during each cell cycle by replication-dependent loss of DNA termini. Although maintenance of telomere length is critical for cell-replicative potential and tumourigenesis, the erosion of telomeres can lead to genetic instability, a pivotal mechanism in the neoplastic process. PATIENTS AND METHODS: A total of 118 colorectal cancer (CRC) samples (53 right-colon, 30 left-colon, and 35 rectal tumours) and corresponding adjacent non-canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
121
10
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(150 citation statements)
references
References 38 publications
18
121
10
1
Order By: Relevance
“…It has been observed that MMR-deficient cell lines and colon tumors show high mutation frequencies at telomere ends, leading to accelerated telomere shortening. [38][39][40][41] The effect of an increased telomereshortening rate is likely to require early activation of telomerase in such tumors. As hypothesized above, the presence of the A allele of rs2075786 might imply even earlier activation of telomerase.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that MMR-deficient cell lines and colon tumors show high mutation frequencies at telomere ends, leading to accelerated telomere shortening. [38][39][40][41] The effect of an increased telomereshortening rate is likely to require early activation of telomerase in such tumors. As hypothesized above, the presence of the A allele of rs2075786 might imply even earlier activation of telomerase.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Rampazzo and colleagues 10 have studied the association between telomere shortening, genetic instability and site of tumour origin in patients with CRC. 10 They found that telomeres were significantly shorter in CRCs than adjacent normal tissue and that telomere length did not differ with tumour progression or p53 status.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, telomeres limit the capacity of a cell to replicate by inducing senescence as a sort of tumoursuppressing mechanism. 10 Telomerase is an enzymatic ribonucleoprotein complex that acts as a reverse transcriptase and is the main positive regulator of telomere length. Telomerase activity is the most general molecular marker for the identification of human cancer and can be detected in 85%-90% of all tumours.…”
mentioning
confidence: 99%
“…In agreement with our results, Yoshida et al (1997) have detected telomerase in a wide range of malignancies, including those of the gastrointestinal tract, breast and lung. Rampazzo et al (2010) have suggested that telomere shortening is a key initial event in colorectal carcinogenesis, where the extent of telomere erosion is related to the tumour origin site and may be influenced by the mismatch repair pathway. Gonzalo et al (2010) have found that long-standing inflammatory bowel disease in patients with high risk for colorectal cancer leads to an overexpression of human telomerase reverse transcriptase in non-affected colorectal mucosa, suggesting its potential usefulness as a biomarker for the risk of malignant transformation.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, telomeres are considered to be the clock that regulates how many times an individual cell can divide. Telomere sequences shorten each time the DNA replicates until they reach a critically short length, at which point the cell stops dividing and ages (Rampazzo et al 2010). Under normal circumstances, telomerase is active in rapidly dividing embryonic cells and in stem cell populations, but not in terminally differentiated somatic cells.…”
mentioning
confidence: 99%